No Facebook for Me: Examining the Reasons People Choose Not to be on Facebook - Fiebert, Martin S.; Wang, Jamie; Warren, Christopher R (Advances in Social Sciences Research Journal, 2018)
For several years, research has investigated a number of variable associated with behavior on social networking and the proclivity toward its use. the present study explores some of the reasons people choose not to join one social networking site, Facebook (FB). A convenience sample consisting of 91 women and 58 men, none of whome were on FB, responded to a 13-item survey offering possible reasons for their not participating. Responses disclosed four core concerns: privacy, preference for personal interactions, superficiality of FB, and time constraints. For these reasons subjects chose either to leave or not to join FB. Age and gender were analyzed as well, illustrating minimal differences.